Effect of structural parameters of spindle system of ultra-high speed grinder on critical speed and vibration mode. (1st January 2012) - Li, C.H.; Wang, S.; Ding, Y.C.
Based on the transfer-matrix method and taking into consideration the gyroscopic couple, the shear, the variable cross-section and other influential factors, a dynamic model was established for the multi-disk rotor of the rotor-bearing system of the grinder spindle. The critical speeds of first three orders, the modes of variation and other dynamic characteristic parameters of the grinder spindle were calculated. The influences of the axial pre-tightening force of the bearing, the span of the fulcrum bearing as well as the changes in the front and rear overhangs on the critical speed of the rotor-bearing system on the grinder spindle and their pattern of changes were analysed. The results showed that the working speed of the spindle system is much lower than the primary critical speed and can therefore stay away the resonance range effectively. Furthermore, the span of the fulcrum bearing and the overhang had significant influences on the critical speed within a certain range.